Desenvolvimento de sistemas biomiméticos para detecção de íon cianeto e do metabólito do diuron, a 3,4-dicloroanilina, em análises ambientais - Figueira, Eduardo Carneiro [UNESP] (2017)
The present study is based on the construction of biomimetic sensors for the sensitive and selective determination of two pollutants, the cyanide ion, which is released into the environment through effluents from the metallurgical industry and 3,4-dichloroaniline, the metabolite of the herbicide diuron that causes alteration of the endocrine system, widely used in agriculture. For the development of biomimetic sensors, carbon paste-based electrodes have been modified with complexes that mimic the active site of the P450 enzymes. The complexes that presented biomimetic profile and better analytical performance in the voltammetric determination of cyanide and 3,4-dichloraniline were respectively 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanincobalt (II) [Co(II)PcF16] and phthalocyaninecopper (II) [Cu(II)Pc]. The sensor constructed for the determination of the cyanide ion presented the best responses using sodium hydroxide 0.5 mol L-1 pH 12.0 and 15% w/w of the [Co(II)PcF16] complex as the support electrolyte, using square wave voltammetry at 20 Hz frequency, 10 mV amplitude and 10 mV potential increase (ΔEs). With the optimized parameters, the sensor had a linear response range of 2.4 x 10-5 mol L-1 to 1.7 x 10-4 mol L-1 and limits of detection and quantification of 1,1 x 10-5mol L-1 and 3,6 x 10-5 mol L-1, respectively. The best results for the 3,4-dichloroaniline herbicide were obtained in Britton-Robinson 0.1 mol L-1 pH 5.0 buffer and 15% w/w [Cu(II)Pc] using square wave voltammetry at 30 Hz frequency, 100 mV amplitude and 5 mV potential increase (ΔEs). Under optimized conditions, the sensor presented a linear response range of 2.8 x 10-5 to 3.0 x 10-4 mol L-1 and limits of detection and quantification of 1,1 x 10-5 mol L-1 and 3,7 x 10-5 mol L-1, respectively. The biomimeticity of the sensors were also evaluated, exploring the hyperbolic profile of each response, scan rate and interferences. The sensors were satisfactorily used in the analyzes in environmental samples, such as river waters. They are presented as advantageous alternatives in relation to other available methods, due to proposed methodologies allowed a low consumption of reagents, present low cost, simplicity, quick and do not require specific or complicated procedures for sample preparation.